Organic Room‐Temperature Phosphorescence with Strong Circularly Polarized Luminescence Based on Paracyclophanes - Liang, Xiao; Liu, Ting‐Ting; Yan, Zhi‐Ping; Zhou, Yan; Su, Jian; Luo, Xu‐Feng; Wu, Zheng‐Guang; Wang, Yi; Zheng, You‐Xuan; Zuo, Jing‐Lin (Angewandte Chemie International Edition, 2019)
Pure organic materials with intrinsic room‐temperature phosphorescence typically rely on heavy atoms or heteroatoms. Two different strategies towards constructing organic room‐temperature phosphorescence (RTP) species based upon the through‐space charge transfer (TSCT) unit of [2.2]paracyclophane (PCP) were demonstrated. Materials with bromine atoms, PCP‐BrCz and PPCP‐BrCz, exhibit RTP lifetime of around 100 ms. Modulating the PCP core with non‐halogen‐containing electron‐withdrawing units, PCP‐TNTCz and PCP‐PyCNCz, successfully elongate the RTP lifetime to 313.59 and 528.00 ms, respectively, the afterglow of which is visible for several seconds under ambient conditions. The PCP‐TNTCz and PCP‐PyCNCz enantiomers display excellent circular polarized luminescence with dissymmetry factors as high as −1.2×10−2 in toluene solutions, and decent RTP lifetime of around 300 ms for PCP‐TNTCz enantiomers in crystalline state. A series of organic phosphors based on paracyclophanes (PCPs) exhibit both strong room‐temperature phosphorescence (RTP) and excellent circularly polarized luminescence. Modulating the PCP core with non‐halogen‐containing electron‐withdrawing units elongates the RTP lifetime to 313.59 and 528.00 ms. The afterglow is visible for several seconds under ambient conditions.